2015
DOI: 10.1038/ncomms9965
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature in situ nuclear spin hyperpolarization from optically pumped nitrogen vacancy centres in diamond

Abstract: Low detection sensitivity stemming from the weak polarization of nuclear spins is a primary limitation of magnetic resonance spectroscopy and imaging. Methods have been developed to enhance nuclear spin polarization but they typically require high magnetic fields, cryogenic temperatures or sample transfer between magnets. Here we report bulk, room-temperature hyperpolarization of 13C nuclear spins observed via high-field magnetic resonance. The technique harnesses the high optically induced spin polarization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
137
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(138 citation statements)
references
References 37 publications
1
137
0
Order By: Relevance
“…Enhancements of ≈2 × 10 5 have been observed for optically pumped microwave-driven DNP using NV − at low fields [9], and approximately 45 at high field via sample shuttling [56]: the primary advantage of the present work is projected field-insensitivity without the requirement for expensive highfrequency microwave components (>200 GHz), cryogenics, or sample shuttling at typical NMR fields.…”
Section: Polarization Efficiencymentioning
confidence: 81%
See 1 more Smart Citation
“…Enhancements of ≈2 × 10 5 have been observed for optically pumped microwave-driven DNP using NV − at low fields [9], and approximately 45 at high field via sample shuttling [56]: the primary advantage of the present work is projected field-insensitivity without the requirement for expensive highfrequency microwave components (>200 GHz), cryogenics, or sample shuttling at typical NMR fields.…”
Section: Polarization Efficiencymentioning
confidence: 81%
“…The development of a general nuclear hyperpolarization technique at arbitrary fields would enable measurements of biomolecules and reaction dynamics that were not accessible by the present techniques while decreasing routine NMR measurement times by orders of magnitude [1]. Several approaches to dynamic nuclear polarization (DNP) processes have been demonstrated that enhance nuclear spin polarization; however, the majority are limited to specific fields [2][3][4][5], low temperatures [6,7], specific molecules [8], or require microwave irradiation of the sample [8,9]. Low temperature is particularly problematic for liquid-state biological samples, where freezing leads to a loss of spectral resolution [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, hyperpolarization can boost magnetic resonance signals because it increases the polarization by a factor of 10 4 –10 5 compared with thermal equilibrium. For example, a 170,000-fold enhancement compared with thermal equilibrium was recently reported for bulk nuclear spin polarization of 13 C from optically pumped nitrogen-vacancy centres in diamond 14 . Other hyperpolarization methods include spin-exchange optical pumping (by 3 He and 129 Xe) 15,16 , metastability-exchange optical pumping 17 , dynamic nuclear polarization 18 and parahydrogen-induced polarization 19 .…”
Section: Imaging Modalitiesmentioning
confidence: 87%
“…A difference in intersystem crossing rates between the m s =0 and m s =±1 excited state levels results in spin polarization into the m s =0 sublevel upon optical pumping [2]. NV-centers have applications in numerous fields, including magnetometry [3], nuclear spin polarization [4][5][6][7][8][9][10][11][12], and quantum information processing [13]. While many applications utilize single defects aligned with an applied magnetic field, understanding orientation dependence of NV-polarization is important for applications involving ensembles of defects in single crystals as well as defects in nanodiamonds.…”
Section: Introductionmentioning
confidence: 99%